Endoscopic nasobiliary drainage tube insertion for treatment of afferent loop obstruction in a pregnant woman after Kasai portoenterostomy - Ken-ichiro Konishi; Kan Suzuki; Makoto Komura; Hiroki Kudo; Tetsuya Ishimaru; Masahiko Sugiyama; Hiroaki Komuro; Tadashi Iwanaka; Jun Fujishiro (Elsevier, 2022)
Afferent loop obstruction (ALO) is a rare complication of Kasai portoenterostomy (KPE) for biliary atresia. A 23-year-old Japanese woman who had undergone KPE with Roux-en-Y reconstruction for biliary atresia at age 42 days experienced intermittent abdominal pain during pregnancy. From computed tomography findings, she was diagnosed with ALO of the Roux-en-Y limb due to obstruction at the jejunojejunostomy. At 22 weeks of gestation, we inserted an endoscopic nasobiliary drainage (ENBD) tube into the dilated Roux-en-Y limb during double-balloon small-bowel endoscopy for treatment of the ALO. As no findings of jejunojejunostomy obstruction were evident during the endoscopy, we consider the obstruction was caused by flexion of the jejunojejunostomy associated with pregnancy. The ENBD tube afforded good drainage, and decompression of the Roux-en-Y limb was confirmed. We waited until 28 weeks of gestation to remove the ENBD tube, considering both the durability of ENBD tube and continued safety of the fetus. At 39 weeks of gestation, the patient delivered of a live baby boy (2,864 g) via vaginal delivery. ENBD tube insertion could be a minimally invasive option for treating ALO during pregnancy after KPE with Roux-en-Y reconstruction.